2017
DOI: 10.1021/acs.energyfuels.7b01848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of KCl and SO2 on NO Formation in C3H8 Flames

Abstract: The use of low-quality fuels in power generation plants is typically motivated by the potential for reducing fuel costs or CO2 emissions, the latter in the case of a fuel based on biomass. These features make low-quality fuels attractive, although their use for power generation is usually problematic due to their composition. One of the main issues is high-temperature corrosion (HTC), which is caused by alkali-containing chlorides. The alkali chlorides, which are formed from alkali metals and chlorine released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The concentration of CO is chosen for tuning the model since CO is an important indication of the local stoichiometry in the experimental flame. This method has been applied successfully in previous studies [44,45] to describe the combustion conditions and the chemistry of nitrogen, sulfur and alkali as well as hydrocarbon oxidation. In the case of Air-32, temperature measurements were not available due to measurement issues related to large amounts of soot clogging the suction pyrometer.…”
Section: Interpretation Of Experimental Resultsmentioning
confidence: 99%
“…The concentration of CO is chosen for tuning the model since CO is an important indication of the local stoichiometry in the experimental flame. This method has been applied successfully in previous studies [44,45] to describe the combustion conditions and the chemistry of nitrogen, sulfur and alkali as well as hydrocarbon oxidation. In the case of Air-32, temperature measurements were not available due to measurement issues related to large amounts of soot clogging the suction pyrometer.…”
Section: Interpretation Of Experimental Resultsmentioning
confidence: 99%
“…Propane was used as fuel, with λ of 1.15 and with a resulting flue gas composition composed of 11.8 vol % CO 2 (dry), 2.95 vol % O 2 (dry), and 14.6/13.6 vol % H 2 O, for operation with and without liquid injection, respectively. The used operating conditions are consistent with established conditions used in previous work, in which a detailed temperature profile and gas composition are available . Alkali salts are injected as a liquid, and the flow rate is set and monitored using a pump (delta 1612, ProMinent).…”
Section: Methodsmentioning
confidence: 99%
“…The used operating conditions are consistent with established conditions used in previous work, in which a detailed temperature profile and gas composition are available. 5 Alkali salts are injected as a liquid, and the flow rate is set and monitored using a pump (delta 1612, ProMinent). To achieve a stable reference concentration, 0.9 L h −1 KCl(aq) with a concentration of 3.34 wt % was injected, which corresponds to 100 ppm of KCl in the flue gas, assuming complete combustion and that all injected KCl remains as KCl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has, for example, been shown that the injection of KCl (aq) in a propane flame can both influence fuel oxidation and depress the formation of NO. It was also shown that the effect of injection could change from inhibiting to promoting, depending on the combustion conditions. , Another study focused on the recirculation of a liquid containing H 2 SO 4 in a full-scale waste-to-energy plant . It was found that it had a clear effect on the aerosol and deposition formation in terms of reduced corrosion and the deposition growth rate.…”
Section: Introductionmentioning
confidence: 99%